Psychiatric morbidity in children attending child guidance clinic in a tertiary care teaching hospital - C., Ramya; K., Pavan Kumar; S., Karthik (International Journal of Contemporary Pediatrics, 2020)
Background: Mental health and its related problems are growing concerns over the world. The early onset of emotional and behavioral problem in the young children is related to a variety of health and behavior problems in adolescence and later life as well. Most of these children present to Pediatric outpatient clinics owing to the Stigma and lack of awareness. The aim of the study is to find out the pattern and prevalence of psychiatric morbidity in children presenting to pediatric outpatient clinics. Methods: It is a cross sectional, point prevalence study of children who have attended Child Guidance Clinic of Pediatric Department in a tertiary care teaching hospital October 2019 to January 2020. Clinical and demographic details was collected in a semi-structured proforma and the details were analyzed. Results: A total of 114 children were analyzed during the study period and this study comprised of 62 boys and 52 girls. Most of the children belonged to the age group of 11-15 years (51%) followed by the ages of 6-10(29.8%). Most common reason for consultation was change in behavior, school refusal and poor academic performance. The most common diagnosis made was Dissociative Conversion Disorder (17.6%), Nocturnal enuresis (15.7%), Mild Mental Retardation (10.5%) and Seizure Disorder with Behavioral Problems (10.5%). Conclusions: A significant number of children attending the Paediatric OPD of general hospitals have psychiatric disorders. The emotional and behavioral problems in children often present with physical symptoms. An effective liaison of services will help to identify and treat children with psychiatric morbidity.